In Vitro Transdifferentiation Potential of Equine Mesenchymal Stem Cells into Schwann-Like Cells - Ferreira, Lucas Vinicius de Oliveira; Kamura, Beatriz da Costa; Oliveira, Joao Pedro Marmo del; Chimenes, Natielly Dias; Carvalho, Marcio de; Santos, Leandro Alves dos; Dias-Melicio, Luciane Alarcao [UNESP]; Amorim, Renee Laufer; Amorim, Rogerio Martins [UNESP] (Mary Ann Liebert, Inc, 2023)
Schwann cells (SCs) are essential for the regenerative processes of peripheral nerve injuries. However, their use in cell therapy is limited. In this context, several studies have demonstrated the ability of mesenchymal stem cells (MSCs) to transdifferentiate into Schwann-like cells (SLCs) using chemical protocols or co-culture with SCs. Here, we describe for the first time the in vitro transdifferentiation potential of MSCs derived from equine adipose tissue (AT) and equine bone marrow (BM) into SLCs using a practical method. In this study, the facial nerve of a horse was collected, cut into fragments, and incubated in cell culture medium for 48 h. This medium was used to transdifferentiate the MSCs into SLCs. Equine AT-MSCs and BM-MSCs were incubated with the induction medium for 5 days. After this period, the morphology, cell viability, metabolic activity, gene expression of glial markers glial fibrillary acidic protein (GFAP), myelin basic protein (MBP), p75 and S100 beta, nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and glial cell-derived neurotrophic factor (GDNF), and the protein expression of S100 and GFAP were evaluated in undifferentiated and differentiated cells. The MSCs from the two sources incubated with the induction medium exhibited similar morphology to the SCs and maintained cell viability and metabolic activity. There was a significant increase in the gene expression of BDNF, GDNF, GFAP, MBP, p75, and S100 beta in equine AT-MSCs and GDNF, GFAP, MBP, p75, and S100 beta in equine BM-MSCs post-differentiation. Immunofluorescence analysis revealed GFAP expression in undifferentiated and differentiated cells, with a significant increase in the integrated pixel density in differentiated cells and S100 was only expressed in differentiated cells from both sources. These findings indicate that equine AT-MSCs and BM-MSCs have great transdifferentiation potential into SLCs using this method, and they represent a promising strategy for cell-based therapy for peripheral nerve regeneration in horses.
Keywords: facial nerve; nerve regeneration; neurotrophic factors; peripheral nerve injury; Schwann-like cells